Comparison of Video Conference Applications Performed Through Two Different Methods Using Frame Relay Line - Das, Resul; Varol, Asaf (Gazi Univ, 2005)
Video conference is a real time communication method which enables people in two or more different places can communicate using voice or image facilities via various tools. Video conference applications offer the synchronous facilities such as the meeting, education or conference at the same time. In this work, two different conference application methods are used for distance education. The first application performed between Firat and Akdeniz universities via university's internet connection (ULAKBIM, National Acedemic Network and Information Center) assigning a bandwidth. In the second method, a video conference application has been utilized via external bandwidth from Firat University to Anadolu University, point to point. Router configuration and adjustment of parameters used in these applications have been compared for these two different methods. The bond connection schemas of applications have been drawn and according to the results of the equal bandwidths the two applications were compared together. Finally, some suggestions and recommendations are offered.
Keywords: Campus Networks; Video Conference; Distance Education